صور من الشذوذ الجنسي المحرمة في القرآن الكريم والسنة النبوية وأضراره والحكمة من تحريمه: Examples of Contradictory Sexual Practice That is Prohibited in The Noble Qurʾān and Sunnah: Its Harms and the Wisdom of Its Prohibition - Ahmed Ibrahim Mahmoud Ahmed; Muhammad Arif Musa (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The concept of homosexuality is considered as sexual practice contrary to the normal instincts that God gave people, and unfortunately, homosexuality has spread in Western societies on a large scale. This concept is met with great approval by Western people, resulting in spite and hatred by this group to Islam and Muslims as a whole Making things worse, a group of so-called Islamic thinkers and researchers has emerged to defend this heinous crime by interpreting legal texts according to their desires. Hence, this research aims to explain the Qurʾānic verses and authentic Prophetic hadiths on homosexuality, demonstrating the invalidity of this concept and proving that it is a deviation from nature intended by God Almighty to humans and cannot be deemed as a human right. Undoubtedly homosexuality has dire consequences on individuals and societies. In this study, the researcher referred to many important sources (i.e., texts of the Noble Qurʾān, Sunnah of the Prophet, books of exegesis, explanations on books of the four schools of thought, and others) that deal with the issue.